Synthesis of TiO2-SnO2 Using Solvothermal as Photoelectrode Dye Sensitized Solar Cell - MOSTAVAN - NIM. 23315303 , ALBAYRUNI
Photoelectrodes in dye-sensitized solar cells have an important role in the process of electron transfer. Where this photoelectrode comes from an oxide compound such as TiO2, SnO2, ZnO, and others. The metal oxides used are usually in the size of nanoparticles. To obtain the metal size of osida nanoparticles can be used in several processes such as sol-gel, chemical vapor deposition (CVD), physical vapor deposition (PVD), sonochemical, hydrothermal, and solvothermal. In the photoelectrode study that will be used in DSSC using metal oxide from the results of synthesis by solvothermal method. Where the metal oxides used are TiO2, SnO2, and variations of the mixture between TiO2 and SnO2 with a ratio of 3: 1, 1: 1, and 1: 3. This photoelectrode is made into a layer over FTO conductive glass using the spin coating method. The purpose of this photoelectrode research using metal oxide is to improve the performance of photoelectrodes in DSSC by mixing two kinds of oxide compounds, namely TiO2 and SnO2. Because if in one of the compounds used as photoelectrodes such as TiO2 compounds, there is a deficiency in the speed of electron transport, whereas in SnO2 compounds there is a deficiency in adsorbing dye on the surface but has advantages in stability and minimizes dye degradation lanes and has better electron mobility compared to TiO2. In this solvothermal process, TiO2, SnO2, and a mixture of TiO2-SnO2 were obtained based on XRD test results with visible intensity peaks indicating that there were crystals from both compounds. In the SEM test results, the average size of metal oxide is 30-100 nm in round shape which is agglomerated with other particles in the sample with TiO2 metal oxide and 1-4 micrometers shaped like a ball on a sample with SnO2 metal oxide. When in the spraying of both TiO2 and SnO2 metal oxides there are both sizes, so that in this photoelectrode produces an effect as a scattering layer. The value of the bandgap obtained by using the tauch plot method on the results of UV-Vis Spectroscopy test shows that there is a change in bandgap value and also the conduction band boundary in each sample which is tested where on TiO2 3.2 eV and SnO2 3.15eV, when mixing the two are increased bandgap that is the ratio of TiO2 and SnO2 3: 1 is 3.23eV, 1: 1 is 3.27eV, and 1: 3 is 3.3eV. For the performance of the DSSC using TiO2, SnO2, and the metal oxide mixture has different values using the results of the EIS test and also the I-V. The EIS results obtained an electron transport resistance value in metal oxide, recombination resistance, electron life time, electron extraction time, chemical diffusion efficiency, and effective diffusion length which play an important role in the ability to convert energy from light into electricity. In the ability to convert which is seen using I-V, the most optimal performance is found in the mixture between TiO2 and SnO2 3: 1. With the highest efficiency of 1.53% in the mixture of TiO2 and SnO2 3: 1 because the transport resistance value decreases compared to TiO2 and because there are two different sizes produce scattering layer to scatter the light so that the dye captures more light. However, at a higher fill factor value, the photoelectrode uses TiO2 without a mixture with a value of 0.66. However, if a larger number of sizes can be seen in a mixture of a ratio of 1: 1 and 1: 3 in TiO2 and SnO2 metal oxides, the dye sticks less to the oxide oxide so that the performance value is not higher than the 3: 1 mixture.